2013
DOI: 10.1111/ctr.12262
|View full text |Cite
|
Sign up to set email alerts
|

Allotransplanting donor kidneys after resection of a small renal cancer or contralateral healthy kidneys from cadaveric donors with unilateral renal cancer: a systematic review

Abstract: This systematic review summarizes evidence on allotransplantation of donor kidneys after resection of a small renal cancer or contralateral healthy kidneys from cadaveric donors with unilateral renal cancer. Eligible studies were identified by screening four bibliographic databases, contacting key authors, and analyzing the bibliographies of included studies. Two reviewers independently assessed the reports for inclusion and extracted data, which were summarized as a narrative review. In the 20 case report or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our results are in line with recent studies that have supported the feasibility of considering the use of organs from donors with small RCC resected prior to transplant. Yu et al found no evidence of RCC recurrence in 97 cases with pre‐transplant RCC resection. One example of recurrence occurred in 22 cases in which the contralateral kidney was used.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with recent studies that have supported the feasibility of considering the use of organs from donors with small RCC resected prior to transplant. Yu et al found no evidence of RCC recurrence in 97 cases with pre‐transplant RCC resection. One example of recurrence occurred in 22 cases in which the contralateral kidney was used.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplant by using a restored kidney graft after ex vivo excision of a tumour has been reported as a novel source [16,19–22,25]. The tumour was usually an incidental finding during deceased donor kidney procurement or live donor workup.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tumour recurrence is associated with the tumour size and its Fuhrman grade. The kidney graft with a tumour at Fuhrman grade IV should not be recommended for transplantation as the high risk of tumour recurrence [21,25,33].…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation is associated with a low but unavoidable risk of cancer transmission [1–3]. Physical examination and CT scan are routinely performed to detect unknown malignancy before donation, but some cancers, such as gallbladder cancer (GBC), can be difficult to rule out.…”
Section: Variables Case 1 Case 2 Casementioning
confidence: 99%